2019
DOI: 10.3390/medicina55060293
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage Stage versus Blastocyst Stage Embryo Transfer in Oocyte Donation Cycles

Abstract: Background and Objective: During the last few years, a trend has been noted towards embryos being transferred at the blastocyst stage, which has been associated with improved rates regarding implantation and clinical pregnancy in comparison to cleavage stage embryo transfers. There is a limited number of studies investigating this notion in oocyte donation cycles employing cryopreserved embryos. The aim of this study is to evaluate the implantation potential and clinical pregnancy rates between the day 3 cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Moreover, the study did not limit the type of ET, including cleavage-stage or blastocyst-stage ET, or the number of transferred embryos. According to current research, there may be differences in clinical and neonatal outcomes between cleavage-stage and blastocyst-stage embryo transfers (22)(23)(24). Moreover, the effect of the number of transferred embryos on pregnancy outcome is relatively clear (25,26).…”
Section: Comparisons With Other Reportsmentioning
confidence: 99%
“…Moreover, the study did not limit the type of ET, including cleavage-stage or blastocyst-stage ET, or the number of transferred embryos. According to current research, there may be differences in clinical and neonatal outcomes between cleavage-stage and blastocyst-stage embryo transfers (22)(23)(24). Moreover, the effect of the number of transferred embryos on pregnancy outcome is relatively clear (25,26).…”
Section: Comparisons With Other Reportsmentioning
confidence: 99%
“…Therefore, we suggest that the higher live birth rate we observed in the D5 ET group when all patients were analyzed together arose due to the differences in the cycle outcome in the group of patients younger than 36 years. In addition, some other studies have suggested that the rate of live birth is higher if ET in performed on day five [ 8 , 9 , 10 , 11 , 12 ], and the miscarriage rate is lower [ 11 , 13 , 14 ], but it is not clear if the cumulative LBR is also higher [ 8 ]. In contrast, other studies have indicated that there is no difference in the pregnancy or live birth rates [ 3 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In assisted reproductive technology cycles, embryos can be transferred during the cleavage stage and the blastocyst stage. Several meta-analyses have shown that blastocyst transfers have a higher implantation rate (IR) than cleavage-stage embryo transfers [1,2]. Single blastocyst transfer (SBT) is becoming widely popular due to tocysts and D6 high-quality blastocysts, and it has been unclear which is the better choice.…”
Section: Introductionmentioning
confidence: 99%